An overview on the role of CO2 laser in general dermatology. Issue 2 (24th January 2021) - Conforti, Claudio; Vezzoni, Roberta; Giuffrida, Roberta; Fai, Annatonia; Fadda, Sara; Marangi, Giovanni Francesco; Persichetti, Paolo; Piccolo, Domenico; Segreto, Francesco; Zalaudek, Iris; Dianzani, Caterina
Abstract: Among different laser types, the carbon dioxide (CO2 ) laser remains one of the most used by dermatologists. Its usefulness has been demonstrated both for therapeutic and cosmetic purposes. This review aims to provide an overview of the applications of CO2 laser in dermatology, focusing on the treatment of infective, neoplastic, and antiaesthetic lesions.